Effect of Dosage and Frequency of Fertilization Application Potassium in Lowland Melon (Cucumis melo L.) Cultivation in Polybags - Viona Rahmadhanti; Nurlianti Nurlianti; Sunarti Sunarti; Sri Rustianti; Asfaruddin Asfaruddin (The University of Lampung, 2024)
Melon cultivation is usually cultivated in the highlands, but the development of melon cultivation in the lowlands has the potential to be developed. The problem is that ultisol with low fertility dominates the soil in the lowlands. Cultivating melons in polybags makes it possible to provide ideal nutrients for plant needs. The right frequency of fertilization can provide appropriate nutrients for each phase of plant growth. The study aimed to determine the best dose and frequency of potassium fertilizer application and the interaction between the two on the growth and yield of melon plants and the sweet taste of melons. The study used a randomized block design (RBD). Factor I: Potassium dose (D) 4 levels: control: 0 g per plant, D1: 30, D2: 40, D3: 50. The second factor is the frequency of application of Potassium (F) consisting of 3 levels, namely: F1: 4 times, F2: 6, and F3: 8. The results of the study showed that the frequency of application of potassium fertilizer had a significant effect on the flowering age of melon plants. A potassium fertilizer dose of 50 g per plant (D3) gave the best fruit weight and diameter and a higher sweetness than other treatments. Keywords: Lowland, Fertilization frequency, Polybag cultivation, Potassium dosage.